2013
DOI: 10.1007/s12031-013-0090-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vitamin A Supplementation on RAR Gene Expression in Multiple Sclerosis Patients

Abstract: Vitamin A and its derivatives have been shown to modulate the immune system via retinoic acid receptor (RAR). This study explored the impact of retinyl palmitate supplementation on RAR subtype gene expression in peripheral blood mononuclear cells (PBMCs) in multiple sclerosis (MS) patients. The study designed as a double-blind randomized clinical trial in which relapsing remitting multiple sclerosis patients were evaluated. Both groups received one capsule 50,000 IU vitamin D3 per 2 weeks and one intramuscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 32 publications
1
43
0
3
Order By: Relevance
“…Indeed, vitamin A has been proposed to derive intrinsic immunoregulation within the CNS tissue under the MS condition [ 99 ]. RA is intrinsically produced by the reactive astrocytes that exhibit upregulated RALDH2 expression.…”
Section: Efficacies Of Ra In the Treatment Of Autoimmune Diseasesmentioning
confidence: 99%
“…Indeed, vitamin A has been proposed to derive intrinsic immunoregulation within the CNS tissue under the MS condition [ 99 ]. RA is intrinsically produced by the reactive astrocytes that exhibit upregulated RALDH2 expression.…”
Section: Efficacies Of Ra In the Treatment Of Autoimmune Diseasesmentioning
confidence: 99%
“…In this regard, we previously reported that vitamin A supplementation (25,000 IU/day for 6 months) led to lower proliferation of myelin oligodendrocyte glycoprotein-reactive lymphocytes in MS patients ). Our team found that vitamin A supplementation results in downregulation of RARα and RARγ in PBMCs of MS patients (Bitarafan et al 2013). Furthermore, vitamin A supplementation significantly reduces IL-17 levels and inhibits gene expression of RORγt , reciprocally promoting TGF-β production and inducing FoxP3 expression in patients with MS (Saboor-Yaraghi et al 2015).…”
Section: Vitamin a Deficiency And Msmentioning
confidence: 89%
“…Previously, it was shown to inhibit oligodendrocyte maturation during CNS myelination [32] , and known as a negative regulator through an RAR-dependent mechanism in the PNS [33] , but the down-regulators involved in this inhibitory signaling were not determined. It has been demonstrated that RARα and RARγ were down-regulated in peripheral blood mononuclear cells (PBMC) from MS patients who take dietary vitamin A daily [34] . The analyses of the biology of RA have focused mostly on its interaction with the immune system as shown by the large number of clinical studies using RA as a supplement [35] .…”
Section: Discussionmentioning
confidence: 99%